2021
DOI: 10.3390/ijgi10090579
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factor Detection for Tourism on the Qinghai-Tibet Plateau Based on Social Media Data

Abstract: Tourism is playing an important role in the economic development of the Qinghai-Tibet Plateau (QTP). To better develop tourism in this region, the spatial heterogeneity of influencing factors on tourism needs to be studied. Using the spatial distribution of tourism potential from social media data, this paper analyzes the influencing factors of tourism on the QTP from the perspective of spatial heterogeneity. We extract microblogs related to travel topics connected to the QTP in 2017 from Sina Weibo to capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this study, the FNF was obtained through the mass balance and N flow calculation method, which only includes three subsystems: the CPS, LBS and HCS. Furthermore, since the operation of the Qinghai‐Tibet Railway in 2006, the number of tourists has rapidly increased (Hu et al., 2021 ). From national statistical data, in 2018, the number of tourists reached 42.04 million and 33.69 persons‐time in Qinghai Province and Tibet, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the FNF was obtained through the mass balance and N flow calculation method, which only includes three subsystems: the CPS, LBS and HCS. Furthermore, since the operation of the Qinghai‐Tibet Railway in 2006, the number of tourists has rapidly increased (Hu et al., 2021 ). From national statistical data, in 2018, the number of tourists reached 42.04 million and 33.69 persons‐time in Qinghai Province and Tibet, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for less developed areas, when faced with high‐value natural landscape resources, whether to develop them, in what way to develop them and to what scale and extent to develop them, it is necessary to pay attention to the economic benefits and social benefits while taking into full consideration the comprehensive trade‐off of ecological vulnerability and ecological effects. Unfortunately, existing research and related policies on the Tibetan Plateau either tend to uncontrollably promote the development of tourist facilities in places with high NLAV or implement the most stringent nature protection measures in areas with high ecological vulnerability (Hu et al, 2021; Mou et al, 2022). Clearly, decisions and actions that simply focus on one dimension are one‐sided.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This study found that nature‐based tourism in Tibet increased with traffic accessibility, exhibiting a stronger driving effect than NLAV. Due to the huge investment in transportation on the Tibetan Plateau, local governments and business operators are unable to improve access to the plateau and build the main transportation network, despite their strong desire to develop nature‐based tourism (Hu et al, 2021). Building the transportation system on the Tibetan plateau is entirely the responsibility of the central government (Su & Wall, 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will encourage agricultural regions to transition from traditional energy sources to clean and renewable ones, and optimize fertilizer use and technical management (Yu et al., 2022; Zhuang et al., 2021). Sixth, the cities' scale on the plateau should be rationally planned to remain within the thresholds of resource environmental bearing capacity, and ecological tourism ought to be developed to mitigate summer tourist detriment to the environment (Hu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%